A Study on Kahoot Perception, Competition, and Academic Performance - Maulana, Aditya; Sunarti, Sunarti; Rahmawati, Yeni; Khatimah, Khusnul (Papanda Publisher, 2025)
This study explores the relationship between students’ perceptions of Kahoot, their competitiveness, and academic performance in English learning. The research involved 5 purposively selected 8th grade students from a total of 16 students at a private school in Samarinda. Selection was based on students with the highest academic scores in English. Using a qualitative descriptive approach, data were collected through semi-structured interviews and analyzed using Braun and Clarke’s six-phase thematic analysis. The results revealed that Kahoot was perceived as fun and motivating, with game-like features promoting healthy competition. Students reported academic improvements, particularly in vocabulary and grammar. However, issues such as internet instability and time constraints emerged. Overall, Kahoot enhanced engagement, fostered competition, and supported academic performance in EFL contexts.